2020
DOI: 10.1038/s41593-020-00724-1
|View full text |Cite
|
Sign up to set email alerts
|

Activated microglia cause metabolic disruptions in developmental cortical interneurons that persist in interneurons from individuals with schizophrenia

Abstract: The mechanisms by which prenatal immune activation increase risk for neuropsychiatric disorders are unclear. Here, we generated developmental cortical interneurons (cINs), known to be affected in schizophrenia (SCZ) when matured, from induced pluripotent stem cells (iPSCs) from healthy controls (HC) and SCZ patients, and cocultured them with or without activated microglia. Coculture with activated microglia disturbed metabolic pathways, as indicated by unbiased transcriptome analysis, and impaired mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 55 publications
3
53
0
Order By: Relevance
“…Early aberrant MG activation in cases of PBI may interfere with these cellular processes [ 141 ]. A recent interesting study investigated the specific effects on MG on interneurons derived from iPSC [ 149 ]. This novel study identified that inflammatory-activated MG induced profound changes in the interneurons including compromising energy-dependent neuronal processes such as arborization, synapse formation and synaptic GABA release.…”
Section: Microglia and Other Cellular Brain Partnersmentioning
confidence: 99%
“…Early aberrant MG activation in cases of PBI may interfere with these cellular processes [ 141 ]. A recent interesting study investigated the specific effects on MG on interneurons derived from iPSC [ 149 ]. This novel study identified that inflammatory-activated MG induced profound changes in the interneurons including compromising energy-dependent neuronal processes such as arborization, synapse formation and synaptic GABA release.…”
Section: Microglia and Other Cellular Brain Partnersmentioning
confidence: 99%
“…The authors indeed found increased synapse elimination in cells from patients suffering from SCZ and also implicated minocycline, an antimicrobial chemotherapeutic drug, in the reduction of synapse elimination through microglia ( Sellgren et al, 2019 ). This association was further corroborated by showing persistent changes through microglia in iPSC-derived interneurons of patients suffering from SCZ ( Park et al, 2020 ). Cortical interneurons generated from iPSCs of patients with SCZ also exhibit aberrant arborization and synaptic density, a phenotype that seems to be corrected when applying an inhibitor of protein kinase C ( Shao et al, 2019 ).…”
Section: Neuronal Models For Disorders Of the Brainmentioning
confidence: 70%
“… 12 , 13 Furthermore, our findings are supported by previous studies showing that immune activation of stem cell-derived neurons from healthy individuals result in downregulation of schizophrenia genes 22 and co-culture of stem cell-derived neurons with immune activated microglia give rise to lasting changes in schizophrenia patient interneurons. 23 …”
Section: Discussionmentioning
confidence: 99%